Comparison of manufactured and modeled solar cell - Strachala, D.; Hylský, J. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The aim of the work is to compare the model of monocrystalline silicon solar cell in PC1D with the real solar cell structure in terms of using a model in manufacture process. Real solar cell was firstly measured and analyzed to determine input parameters for a simulation and then realized in free available PC1D software. Degree of conformity of modeled and real solar cell was in the end established for basic prediction of solar cell parameters before manufacturing process.
Keywords: Model of silicon - monocrystalline solar cell; comparison of modeled and real structure; PC1D; manufacturing process